The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1542/peds.2014-3532
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Prevention and Toddler Well-Child Care: Routine Integration in a Safety Net System

Abstract: BACKGROUND AND OBJECTIVE Applying topical fluoride varnish (FV) to young children’s teeth is an effective therapeutic strategy for preventing early childhood caries (ECC). In 2008, the pediatricians at Contra Costa Regional Medical Center and Health Centers became concerned that our low-income pediatric patients had high rates of ECC and very limited access to dental care. We formed an interdisciplinary safety net-academic partnership with the University of California San Francisco to implement routine FV appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Recent studies suggest that including oral health information, such as oral health risk assessments and reminders for oral health referrals, in the electronic health record (EHR) can increase the provision of preventive oral health services in primary care. [9] [10] Although these initial results are promising, most EHRs in primary care settings do not include oral health information for pediatric patients [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that including oral health information, such as oral health risk assessments and reminders for oral health referrals, in the electronic health record (EHR) can increase the provision of preventive oral health services in primary care. [9] [10] Although these initial results are promising, most EHRs in primary care settings do not include oral health information for pediatric patients [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…The two pilot practices were given the option of whether or not to group the oral health questions together; automatic generation of the prescription and list of dentists depended on the capabilities of each practice’s EMR. Quality improvement (QI) studies have found that requiring providers to document the delivery of oral health services in EMR formalizes the behavior and increases the likelihood that it is performed [ 50 , 51 ]. Our pilot study showed that the four oral health questions can be easily incorporated into any practice’s EMR and documented by providers.…”
Section: Discussionmentioning
confidence: 99%
“…All of these results reflect that the knowledge and information provided by the current OHE in Shandong Province appears to be inefficient and that it underperforms in promoting the implementation of ECC prevention practices. However, many studies have confirmed that when a more systematic, proactive oral health intervention involving brushing training, referrals and dental care is implemented for a family with children, even if implemented by nondental professionals [53], it generally has a greater preventive effect against ECC [46,[54][55][56][57]. Therefore, a systematic and sound oral health care programme that involves clinical care, brushing training, referrals and so on is imperative [58], rather than just oral health education.…”
Section: Logistic Regression Analysesmentioning
confidence: 99%